2020
DOI: 10.7759/cureus.6564
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Hydatid Disease in a Child Involving Multiple Organ Systems: A Case Report

Abstract: Hydatid disease is a parasitic infestation by Echinococcus granulosus, which involves the liver and lungs primarily. The authors report a case of disseminated hydatid disease involving multiple organs simultaneously in a 7-year-old child from Kabul, Afghanistan. The patient under examination had been having a complaint of cough and low-grade fever for the last one year. Computed tomography (CT) and ultrasonography (USG) demonstrated cystic lesions in his liver, lungs, spleen, and suprarenal region. The literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, other sites including the brain, bone, thyroid, muscle, etc. can get infected 4–6 . Intramuscular hydatid cyst accounts for less than 3% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, other sites including the brain, bone, thyroid, muscle, etc. can get infected 4–6 . Intramuscular hydatid cyst accounts for less than 3% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] In the literature, paediatric patients with the multiorgan involvement have been reported as case reports. [13][14][15][16][17][18][19][20][21][22][23] All the current cases of multiorgan involvement are presented in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…3 Cases with the multiorgan involvement presenting with only CNS findings have been reported in the literature. [13][14][15] Cases with the multiorgan involvement presenting with the isolated gastrointestinal symptoms complaining with a chronic cough [16][17][18] and other accompanying respiratory symptoms for an approximately 1 year have been reported. 22 Unlike our cases, three of them were diagnosed incidentally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of hydatidosis mostly depend on the cyst’s size, location, and type and whether it is complicated or not [ 3 ]. Previous studies have reported that abdominal pain, specifically in the right upper quadrant, is the most common symptom of affected patients [ 3 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%